Chapter 6 Kindergarten educators’ affective-motivational dispositions - Vogt, Franziska; Leuchter, Miriam; Dunekacke, Simone; Heinze, Aiso; Lindmeier, Anke; Kuratli Geeler, Susanne; Meier, Anuschka; Seemann, Selma; Wullschleger, Andrea; Moser Opitz, Elisabeth (Taylor & Francis, 2021)
Affective-motivational dispositions regarding the fostering of mathematics are an important aspect of early educators' professional competence, as educators are not following curricular programmes but need to seize moments in everyday activities and in play in order to foster mathematics. A variety of scales measuring variables of affective-motivational dispositions within a questionnaire were employed in a binational study involving 132 kindergarten educators in Germany and Switzerland. Based on the expectancy-value theory of motivation, the relations between educators' emotions regarding mathematics at school, the enthusiasm for mathematics as a subject, the value placed on mathematics and the expectancy of fostering mathematics successfully (self-efficacy) as well as the enthusiasm for fostering mathematics in kindergarten are examined. Following the analysis of correlations and the testing of a multiple regression model, it was found that enthusiasm for mathematics as a subject, importance of mathematics as a subject in kindergarten and self-efficacy predict enthusiasm for fostering mathematics, whereas the variable emotions regarding mathematics at school does not increase the variance explained. Self-efficacy, importance given to mathematics and enthusiasm for fostering mathematics are slightly higher in Switzerland than in Germany, which could be interpreted in light with the structural differences regarding kindergarten.